Microgrid network design and control - Goh, Kok Liang. (2010)
In the time of rapid changes in power industry the need to develop new power systems arises. The newly developed systems should aim at wide utilisation of renewable power sources and CO2-neutral technologies. This goal can be achieved by dissipated generation, or integrating DG into microgrids. The microgrids can be built using AC or DC current networks. Authors propose DC microgrid as a new idea for a small, balanced distribution power system. It has been designed to supply small towns and villages with electricity with high penetration of renewable energy resources. However, designing an optimal microgrid is not an easy task, due to the fact that primary energy carriers are changeable and uncontrollable, as is the demand. Traditional design and optimisation tools, developed for controlled power sources, cannot be employed here. Simulation methods seem to be the best solution. The microgrid consists of several devices, with most important among them - the power electronic devices. The whole work is based upon simulation. Models are made to simulate the different power sources such as PV system, Wind turbine as a storage battery, the electrical loads, and the relevant meteorological conditions, in addition to other items that are needed to represent the autonomous power system satisfactorily.